Pengaruh Pemberian Stretching Exercise Terhadap Tingkat Nyeri Pada Penderita Neck Pain di RSUD Jombang - Umi Hanik Mardiyana; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Ahmad - Abdullah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The purpose of this study was to determine the effect of giving the neck muscles stretching technique to reduce pain in patients with non-specific neck pain.Methods: The research design used is one group pre-test and post-test design. The research subjects were 30 people consisting of 3 men and 27 women with an age range of 20-50 years. Subjects were selected with inclusion and exclusion criteria. Subjects received treatment in the form of stretching exercises for 1 treatment. Stretching exercise program is given for 20-30 minutes each training sessionResults: Based on the results of the data analysis test with the non-parametric Wilcoxon test, p = 0.000 (p <0.005). which means that there is an effect of stretching exercise on pain levels in neck pain sufferers in Jombang Hospital. The results showed that there was an effect of giving stretching exercise to significantly reduce pain in neck pain sufferers.Conclusion: Stretching exercise can reduce neck pain that is mechanical or non-specific, but if the patient returns to his original activities with habits that cause neck pain, then neck pain will reappear. So it can be concluded that stretching exercise can reduce pain in patients with neck pain, if it is done regularly every day with sufficient intensity and duration and added education to avoid activities that trigger neck pain, it will get better results.